Interruption of onchocerciasis transmission in Bioko Island: Accelerating the movement from control to elimination in Equatorial Guinea. - Zaida Herrador; Belén Garcia; Policarpo Ncogo; Maria Jesus Perteguer; Jose Miguel Rubio; Eva Rivas; Marta Cimas; Guillermo Ordoñez; Silvia de Pablos; Ana Hernández-González; Rufino Nguema; Laura Moya; et al. (Public Library of Science (PLoS), 2018)
Onchocerciasis, also known as river blindness, is a parasitic disease. More than 99 percent of all cases occur in Africa. Bioko Island (Equatorial Guinea) is the only island endemic for onchocerciasis in the world. Since 2005, when vector Simulium yahense was eliminated, there have not been any reported cases of infection. This study aimed to demonstrate that updated WHO criteria for stopping mass drug administration (MDA) have been met.A cross-sectional study was conducted from September 2016 to January 2017. Participants were 5- to 9-year-old school children. Onchocerciasis/lymphatic Filariasis (LF, only in endemic districts) rapid diagnostic tests (RDTs) were performed. Blood spots were collected from RDT positive children and 10 percent of the RDT negatives to determine Ov16 and Wb123 IgG4 antibodies through enzyme-linked immunosorbent assay (ELISA). Skin snips were collected from RDT positives. Filarial detection was performed by PCR in positives and indeterminate sera. Black fly collection was carried out in traditional breeding sites. A total of 7,052 children, ranging from 5 to 9 years of age, were included in the study. Four children (0.06%) were Ov16 IgG4 RDT positives, but negative by ELISA Ov16, while 6 RDT negative children tested positive by ELISA. A total of 1,230 children from the Riaba and Baney districts were tested for LF. One child was Wb123 RDT positive (0.08%), but ELISA negative, while 3 RDT negative children were positive by Wb123 ELISA. All positive samples were negative by PCR for onchocerciasis and LF (in blood spot and skin snip). All fly collections and larval prospections in the traditional catching and prospection sites were negative.WHO criteria have been met, therefore MDA in Bioko Island can be stopped. Three years of post-treatment surveillance should be implemented to identify any new occurrences of exposure or infection.